A paradigm shift in the delivery of services for diagnosis of inherited retinal disease. Issue 5 (11th May 2012) - O'Sullivan, James; Mullaney, Brendan G; Bhaskar, Sanjeev S; Dickerson, Jonathan E; Hall, Georgina; O'Grady, Anna; Webster, Andrew; Ramsden, Simon C; Black, Graeme C
Abstract : Objectives: Current technologies for delivering gene testing are labour-intensive and expensive. Over the last 3 years, new high-throughput DNA sequencing techniques (next generation sequencing; NGS), with the capability to analyse multiple genes or entire genomes, have been rapidly adopted into research. This study examines the possibility of incorporating NGS into a clinical UK service context. Methods: The study applied NGS of 105 genes to 50 patients known to be affected by inherited forms of blindness in the setting of a UK National Health Service-accredited diagnostic molecular genetics laboratory. The study assessed the ability of an NGS protocol to identify likely disease-causing genetic variants when compared with current methodologies available through UK diagnostic laboratories. Results: Conventional testing is only applicable to the minority of patients with inherited retinal disease and identifies mutations in fewer than one in four of those patients tested. By contrast, the NGS assay is directed at all patients with such disorders and identifies disease-causing mutations in 50–55%, which is a dramatic increase. This includes patients with apparently 'sporadic' disease, and those for whom clinical management and prognosis are altered as a consequence of defining their disease at a molecular level. Conclusions: The new NGS approach delivers a step change in the diagnosis of inherited eye disease, provides precise diagnostic information and extends the possibility of targeted treatments including gene therapy. The approach represents an exemplar that illustrates the opportunity that NGS provides for broadening the availability of genetic testing. The technology will be applied to many conditions that are associated with high levels of genetic heterogeneity.